The Evolving Idea of Social Responsibility in Bioethics: A Welcome Trend - Ahola-Launonen, Johanna (Cambridge quarterly of healthcare ethics, 2015)
This article discusses the notion of social responsibility for personal health and well-being in bioethics. Although social responsibility is an intrinsic aspect of bioethics, and its role is increasingly recognized in certain areas, it can still be claimed that bioethics in general is committed to an individualistic theoretical framework that disregards the social context in which decisions, health, and well-being are situated. The philosophical premises of this framework regard individuals as rational decisionmakers who can be held accountable for their health conditions and who should be the primary objects of intervention in attempts to reduce lifestyle-associated chronic diseases. There are, however, social determinants of health that challenge this conclusion. Because their impact can be controlled, to a certain extent, by social and public policy decisions, their existence shows the inadequacy of the purely individualistic approach. I suggest, accordingly, that bioethics would benefit, both academically and societally, from a more social perspective. Bioethical studies that acknowledge, from the start, the social determinants of health would be more amenable to constructive multi- and interdisciplinarity, and a more balanced account of responsibility would further the contribution of sound bioethical work to sensible public policies.